Increasing the pump energy efficiency of the system for discharging liquefied natural gas from large-capacity storage facilities via design improvement - A. Yu. Baranov; M. I. Davydenko; Ye. V. Sokolova; O. A. Filatova (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Abstract. Objective. To determine the most relevant way to improve the energy efficiency of the system for discharging liquefied natural gas (LNG) from large-capacity storage facilities. Methods. The method of analysis of existing systems for LNG discharge from storage tanks was used to identify critical (emergency) elements of the system to be improved and possible options of improving structural elements. Results. The operation of the system for discharging LNG from storage tanks was analysed and its main characteristics were described. Main problems associated with designing and building borehole pumps, as well as goals and tasks of designing new borehole pump structures were studied. The main types of LNG borehole pumps, their varieties, and types of drives were studied to choose the most optimal new option of improving pumps for systems for discharging LNG from storage tanks. Further, it will be necessary to calculate geometric parameters of the hydroturbine and operation modes of its wheel being in connection with the centrifugal pump wheel. Conclusion. Experience of using storage facilities shows that LNG pumps are the most critical units significantly increasing production risks. Therefore, the LNG borehole pump design improvement was chosen as a method to increase the energy efficiency of the system for discharging LNG from large-capacity storage facilities. Based on the considered advantages and disadvantages of structural elements of the existing LNG borehole pump design, we chose the replacement of the electric pump drive with an alternative one as the most optimal improvement method.